The role of the Al Ikhlas nursing home in efforts to improve the welfare of the elderly - Nurhayati, Nurhayati; Marvina, Ratna Dina (The International Journal of Politics and Sociology Research, 2023)
This study aims to examine the role of nursing homes in improving the welfare of the elderly. The search results reveal that nursing homes are prone to mistakes and adverse events, and that the physical environment and infrastructure of nursing homes are critical to residents' quality of life. The study recommends that nursing homes collaborate with social services providers, assess the physical, mental, and social health status of the elderly, and explore the role of family involvement in improving the welfare of the elderly. The study also highlights the importance of staff training, adequate staffing levels, and effective communication between staff, residents, and families in improving the quality of care in nursing homes.